Achieving employee commitment for continuous improvement initiatives. Issue 2 (2nd February 2015) - Lam, Marco; O'Donnell, Mark; Robertson, Dan
Abstract : Purpose: – Although prior research has found that employee participation is key to successfully implementing quality management initiatives (Baird et al ., 2011; de Menezes, 2012; Lagrosen and Lagrosen, 2005), little research in operations management exists that investigates which management actions and behaviors lead to employee commitment to such initiatives. The purpose of this paper is to address this gap in the operations management literature by investigating which influence tactics are the most effective in soliciting employee commitment to continuous improvement tasks. The paper also examines how influence tactics affect the supervisor-subordinate relationship and the manager's effectiveness in implementing continuous improvement initiatives. Design/methodology/approach: – A survey instrument was used to measure supervisor-subordinate relationship quality, usage of influence behaviors and participants' task commitment to continuous improvement initiatives. Findings: – The results indicate that five of the 11 influence tactics identified in the prior literature, i.e., collaboration, consultation, ingratiation, inspirational appeals, and rational persuasion, are significant and strong predictors of employee commitment to continuous improvement initiatives. Further, analyses show that these influence tactics are significant drivers of the quality of the supervisor-subordinate relationship, which was found to partially mediate the relationship between influence tactics and the supervisor's effectiveness in implementing continuous improvement projects. Research limitations/implications: – Since the extant CI and Total Quality Management literature has looked at the plant or program level rather than the worker-level as in the research, the findings offer one explanation as to why earlier studies investigating the relationship between quality management programs and increased organizational performance reported mixed results. Practical implications: – Increasing managers' awareness and usage of influence tactics may increase the success rate of continuous improvement projects as well the quality of the relationship with the manager's subordinates. Originality/value: – While the extant literature has argued that management support and employee commitment are key components of a continuous improvement project implementation, little has been written about the specific management actions and behaviors that lead to success.